Thailand’s Alignment Strategy Amidst the US-China Rivalry: A Role Theory Perspective - Han, Wen Chou (วารสารสังคมศาสตร์ จุฬาลงกรณ์มหาวิทยาลัย, 2026)
This paper seeks to analyze how Thailand, as a middle power, navigates its alignment choices amid an intensifying US-China rivalry in the Asia-Pacific region through the lens of role theory. This paper also proposes several original mechanisms to operationalize the role theory in the analysis of Thailand’s strategy. To this end, Thailand’s foreign policy from the past decade (2012 to mid-2025) will be reviewed. The central argument is that Thailand is adopting a “soft hedging” strategy marked by opportunism and driven by its key goal of development, but is, at the same time, complicated by domestic political dysfunction (“fragmented centralism”). Thailand’s foreign policy practice, as a consequence, remains strongly ambivalent. Not only is there no clear positioning of the state in relation to the US-China rivalry and no grand strategy to enhance its strategic autonomy, but there is also no active threat identification. Thailand’s role as an “opportunistic go-between” is both intended and unintended. The former lies in the fact that Thailand aims to leverage its relations with the great powers (and to some degree, other states) to maximize development benefits, while simultaneously preserving its current autonomy in a way that is representative of its historical past, wherein a clear position will only be revealed when a winner is evident in power rivalries. The latter, as indicated by a divergence in domestic preferences as a result of “fragmented centralism,” is self-explanatory in the sense that it does not form part of a calculated, whole-of-government approach.